Quantum Transport and Thermoelectric Properties of InAs/GaSb Superlattices. Issue 1 (1998) - Lin, J.-F.; Ting, D. Z.-Y.
Abstract : In recent years, artificially layered microstructure have been considered as candidates for better thermoelectrics. In this work we examine transport properties of the type-II broken-gap InAs/GaSb superlattice. We use the effective bond orbital model for an accurate description of the band structures. Theoretical results of thermoelectric transport coefficients and the dimensionless figure of merit for an (8, 8)-InAs/GaSb type-II superlattice are presented.